Desenvolvimento de formulação nanoestruturada contendo extrato de Physalis peruviana - Silva, Suelen Santos da (2018)
The use of plant extracts is a growing trend in the food industry and its application depends on the functional properties, availability, cost-effectiveness and their effects on the sensorial attributes of the final product. The bioactive compounds present in the plants may have antioxidant, antimicrobial action, among others, however these compounds have low solubility in water and low stability, which hinders their use and decreases their useful life. The association of nanotechnology with natural products has led to the research and development of nanostructured systems capable of controlling stability, improving solubility, bioavailability and controlling the release of bioactive compounds. The fruit Physalis peruviana is rich in these compounds, therefore, the present work aims the preparation of extracts and the association of these in nanostructured systems, such as nanoemulsion, using high energy preparation method, ultrasound (US). Application of response surface (RSM) methodology to obtain the best condition, varying parameters such as amplitude, sonication time and mass of medium chain triglycerides (MCT). Also the verification of the stability of nanostructured systems, antioxidant and cytotoxic activity. The ideal condition for nanoemulsification was 10 minutes of sonication, in a US bath with a frequency of 37 kHz, with amplitude of 40% and 0.120 g of MCT. The nanoemulsion had a pH of 3.84, a mean droplet diameter of 268±7 nm, a polydispersity index of 0.113 and a negative zeta potential of 13.94 mV. The formulation remained stable over the 60 day period under refrigeration as opposed to the free extract which, after 30 days, lost 56% of phenolic compounds. In vitro and in vivo tests showed that both the free and nanoemulsion associated extracts showed no toxicity. The characteristics of nanoemulsion with developed Physalis peruviana extract as well as non-toxicity suggest safety in the consumption and thus a possible future application in food product.